Creativity, innovations and firm performance in an emerging transition economy - Stojčić, Nebojša (Array, 2018)
Despite the longstanding consensus that creativity is the seedbed of innovation, the limited literature in this area fails to explore the contribution of various aspects of creativity to different stages of the innovation process or the mechanisms used by the management to foster the creativity of employees. This paper adopts a more complex strategy in order to highlight the role of creativity in the entire innovation process from the decision to innovate to investment in innovation, the transformation of innovation input into output and the effect of innovation output on productivity. A multi – stage CDM – type model encompassing different elements of creativity and practices designed to enhance creative potential is applied to the most recent Community Innovation Survey data. In modelling the management of creativity a distinction is made between decisions of firms to hire creative employees and the methods used to foster creativity of personnel such as multidisciplinary work teams, financial incentives and training for creativity. The results indicate that employees with creative skills and the adoption of creativity – enhancing methods by the management are important factors for innovation and better performance of enterprises. They also point to sectoral differences in the impact of creativity on innovation.